2017
DOI: 10.2196/cancer.7312
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Participation in Online Cancer Communities on Patient Reported Outcomes: Systematic Review

Abstract: BackgroundIn recent years, the question of how patients’ participating in online communities affects various patient reported outcomes (PROs) has been investigated in several ways.ObjectivesThis study aimed to systematically review all relevant literature identified using key search terms, with regard to, first, changes in PROs for cancer patients who participate in online communities and, second, the characteristics of patients who report such effects.MethodsA computerized search of the literature via PubMed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 42 publications
1
52
0
1
Order By: Relevance
“…Communities of patients with cancer provide mutual emotional and informational support, which can positively influence quality of life. 7,8 Ziebland and Wyke concluded that this community opportunity was the greatest internet-driven change: "Patients learning to tell the story and visualizing disease." 23 Based on wishes reported in the 2005 study, we hypothesized that approximately 20% of patients with cancer wished to participate in communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Communities of patients with cancer provide mutual emotional and informational support, which can positively influence quality of life. 7,8 Ziebland and Wyke concluded that this community opportunity was the greatest internet-driven change: "Patients learning to tell the story and visualizing disease." 23 Based on wishes reported in the 2005 study, we hypothesized that approximately 20% of patients with cancer wished to participate in communities.…”
Section: Discussionmentioning
confidence: 99%
“…This currently is referred to as e-health. 7,8 Given these major changes in internet use, both in general and for health communication in particular, an important question is to what extent use of the internet by cancer survivors and their wishes for online modalities have changed in recent years. The current study has addressed this question by repeating and extending a study by van de Poll-Franse and van Eenbergen 3 published in 2005, which presented the future wishes regarding the internet of patients with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 The evidence base regarding the effectiveness of online cancer support is modest but positive. 20 Online community use has been reported as a positive experience amongst small samples of cancer survivors in controlled community settings. 21,22 Online community participation has been linked to increased positive coping.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in a prior qualitative study of experiences of individuals with yCRC, participants shared that they often conducted their own independent searches on the Internet for health information on CRC, particularly on topics such as sexual activity, reproductive health, mental health, and work/employment which may not be routinely discussed during healthcare appointments, as well as connect with other patients with CRC in online communities. [20] However, although the Internet has been shown to be bene cial source of information for cancer patients, [20][21][22][23][24] it may also lead to misinformation. [25,26] In 2004, Al-Bahrani & Plusa conducted assessed the quality of websites providing information to individuals with CRC and found that it can be di cult to distinguish accurate, clear information.…”
Section: Discussionmentioning
confidence: 99%